Effect of choline supplementation to corn-soybean meal rations on pig performance - G L Allee (Kansas Agricultural Experiment Station Research Reports, 1977)
Eight-four crossbred gilts initially averaging 8.2 kg. (18.0 lbs.) were used to evaluate the effects of supplemental choline to corns-soybean meal rations on pig performance. Four levels of choline were fed during each ration phase (starter, grower, finisher). The trial was terminated when pigs within a replicate averaged approximately 100 kg. (220lbs.). Supplemental choline had no significant effect on average daily gain or feed efficiency.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Choline; Corn-soybean rations; Performance